"Documenting Tragedy": Ethnography and the (Hidden) Costs of Bearing Witness. (29th November 2018) - Bonet, Sally Wesley; McWilliams, Julia Ann
Abstract : This article examines the affective registers of conducting research with vulnerable populations. We examine the challenges of conducting ethnographies with peoples that are living in conditions of chronic poverty, oppression, and political upheaval. Reversing the ethnographic lens from the participant onto the researcher, we investigate the humanity and the vulnerability of the anthropologist to highlight the emotional journey that accompanies such work.